PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO DAN NET PROFIT MARGIN TERHADAP RETURN SAHAM PADA PERUSAHAAN JASA SUB SEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BEI PERIODE 2012-2018 - Hasanudin Hasanudin; Dipa Teruna Awaloedin (JURNAL REKAYASA INFORMASI, 2020)
This study aims to determine the effect of the variable Current Ratio (CR), Debt to Equity Ratio (DER), Net Profit Margin (NPM) on stock returns simultaneously and partially. Research subjects are telecommunications sub-sector service companies listed on the Indonesia Stock Exchange. This data source uses secondary data in the form of financial statements from each telecommunications company from 2012-2018. The population of this study were 5 telecommunications companies, the sample consisted of 4 telecommunications companies taken using purposive sampling. This study uses multiple linear regression data analysis techniques using the SPSS 23 application. The results of the study show that the Current Ratio, Debt to Equity Ratio and Net Profit Margin variables simultaneously affect stock returns, with a calculated F value of 3.034 with a significant level smaller than 0 .05. Debt to Equity Ratio and Net Profit Margin partially affect stock returns, only the Current Ratio does not affect stock returns with t arithmetic of 0.418 with a significant value of 0, 680, so that the dominant variable influencing stock returns is Debt to Equity Ratio and Net Profit Margin Keywords : Return Saham, Current Ratio, Debt to Equity Ratio, Net Profit Margin